Answer:
x=-3,x1/2
Step-by-step explanation:
f(x)=(2x-1)(x+3)
TI find x intercept/zero substitute
f(x)=0
0=(2x-1)x(x+3)
swap the sides of the equation
(2x-1)x(x+3)=0
when the product of factors equals 0,at least one factor is zero
2x-1=0
x+3=0
solve the equation for x
x=1/2
x+3=0
solve the equation of x
x=-3
The equation has two solution
x=-3
x=1/2
2 3/4 = 2.75
1 1/2 = 1.5
3 3.4 = 3.75
2.75 + 1.5 + 3.75 = 8
You hiked 8 miles last month in total.
Answer: 2 197/1000
Explanation:
(1 3/10)^3
= (13/10)^3
= 13^3/10^3
= 2197/1000
= 2 197/1000
Answer:
$500
Step-by-step explanation:
She pick in $400, she took that $400 out so she would then have $0
She then inserted $500 back in with no money previously
Answer:
Step-by-step explanation:
n+21